International society of sports nutrition position stand: nutritional concerns of the female athlete - Stacy T. Sims; Chad M. Kerksick; Abbie E. Smith-Ryan; Xanne A.K. Janse de Jonge; Katie R. Hirsch; Shawn M. Arent; Susan Joyce Hewlings; Susan M. Kleiner; Erik Bustillo; Jaime L. Tartar; Valerie G. Starratt; Richard B. Kreider; et al. (Taylor & Francis Group, 2023)
Based on a comprehensive review and critical analysis of the literature regarding the nutritional concerns of female athletes, conducted by experts in the field and selected members of the International Society of Sports Nutrition (ISSN), the following conclusions represent the official Position of the Society: 1. Female athletes have unique and unpredictable hormone profiles, which influence their physiology and nutritional needs across their lifespan. To understand how perturbations in these hormones affect the individual, we recommend that female athletes of reproductive age should track their hormonal status (natural, hormone driven) against training and recovery to determine their individual patterns and needs and peri and post-menopausal athletes should track against training and recovery metrics to determine the individuals' unique patterns. 2. The primary nutritional consideration for all athletes, and in particular, female athletes, should be achieving adequate energy intake to meet their energy requirements and to achieve an optimal energy availability (EA); with a focus on the timing of meals in relation to exercise to improve training adaptations, performance, and athlete health. 3. Significant sex differences and sex hormone influences on carbohydrate and lipid metabolism are apparent, therefore we recommend first ensuring athletes meet their carbohydrate needs across all phases of the menstrual cycle. Secondly, tailoring carbohydrate intake to hormonal status with an emphasis on greater carbohydrate intake and availability during the active pill weeks of oral contraceptive users and during the luteal phase of the menstrual cycle where there is a greater effect of sex hormone suppression on gluconogenesis output during exercise. 4. Based upon the limited research available, we recommend that pre-menopausal, eumenorrheic, and oral contraceptives using female athletes should aim to consume a source of high-quality protein as close to beginning and/or after completion of exercise as possible to reduce exercise-induced amino acid oxidative losses and initiate muscle protein remodeling and repair at a dose of 0.32-0.38 g·kg−1. For eumenorrheic women, ingestion during the luteal phase should aim for the upper end of the range due to the catabolic actions of progesterone and greater need for amino acids. 5. Close to the beginning and/or after completion of exercise, peri- and post-menopausal athletes should aim for a bolus of high EAA-containing (~10 g) intact protein sources or supplements to overcome anabolic resistance. 6. Daily protein intake should fall within the mid- to upper ranges of current sport nutrition guidelines (1.4-2.2 g·kg−1·day−1) for women at all stages of menstrual function (pre-, peri-, post-menopausal, and contraceptive users) with protein doses evenly distributed, every 3-4 h, across the day. Eumenorrheic athletes in the luteal phase and peri/post-menopausal athletes, regardless of sport, should aim for the upper end of the range. 7. Female sex hormones affect fluid dynamics and electrolyte handling. A greater predisposition to hyponatremia occurs in times of elevated progesterone, and in menopausal women, who are slower to excrete water. Additionally, females have less absolute and relative fluid available to lose via sweating than males, making the physiological consequences of fluid loss more severe, particularly in the luteal phase. 8. Evidence for sex-specific supplementation is lacking due to the paucity of female-specific research and any differential effects in females. Caffeine, iron, and creatine have the most evidence for use in females. Both iron and creatine are highly efficacious for female athletes. Creatine supplementation of 3 to 5 g per day is recommended for the mechanistic support of creatine supplementation with regard to muscle protein kinetics, growth factors, satellite cells, myogenic transcription factors, glycogen and calcium regulation, oxidative stress, and inflammation. Post-menopausal females benefit from bone health, mental health, and skeletal muscle size and function when consuming higher doses of creatine (0.3 g·kg−1·d−1). 9. To foster and promote high-quality research investigations involving female athletes, researchers are first encouraged to stop excluding females unless the primary endpoints are directly influenced by sex-specific mechanisms. In all investigative scenarios, researchers across the globe are encouraged to inquire and report upon more detailed information surrounding the athlete's hormonal status, including menstrual status (days since menses, length of period, duration of cycle, etc.) and/or hormonal contraceptive details and/or menopausal status.